If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=(-5)C
We move all terms to the left:
-((-5)C)=0
We calculate terms in parentheses: -((-5)C), so:We get rid of parentheses
(-5)C
We multiply parentheses
-5C
Back to the equation:
-(-5C)
5C=0
C=0/5
C=0
| 3(1x+7)-2x=33 | | 5f=4f+3f | | 0.3j-(0.1j-3)+0.1=2(j+0.1)=0.2 | | h+830=270 | | y+1.19=8.33 | | 2(a=1)=3(a+1 | | b-671=138 | | 3y-27=24 | | 2+5(i-3)=7i-15-4i | | v+8=460 | | 15x+35x=0 | | 2/3-8/3y=1/2-5/2y | | 264=b-66 | | 1/2(12x-14)=25 | | (x+4)^2+8(x+4)+16=30 | | 4x-13+28x=26x+3-2x | | -7x-2=54 | | | | | | 1-3x=29 | | 4n+4=89 | | k-949=-457 | | 2x-7√x+8=0 | | -10=q+-923 | | (9x–2)(x+9)=0 | | 2(5x+35)=100 | | d-308=66 | | -5x+7=-11x+5 | | Y=7/8x+7/5 | | -3(3x-4)+4(3x+3)=60 | | -5b-4+2b=8 | | x=4/5=x+2 |